Edukasi Bahaya Rokok dan Napza Remaja SMA Pada Pesantren Ramadhan di Mesjid Nurul Yaqin Kecamatan Koto Tangah Padang - Dewi Yudiana Shinta; Melly Siska Suryani; M. Diki Juliandi; Merry Threesia; Mulyadi Mulyadi; Herix Sonata MS; Givansyah Maizola (CANANG: Jurnal Pengabdian Masyarakat, 2024)
Cigarettes and drugs damage a person's mind and mental health, it also makes a person addicted and addicted so that it justifies any means to get it. This activity aims to increase the knowledge of high school adolescents about the dangers of smoking and drugs for themselves. The benefit of this activity is to make them understand the dangers of smoking and drugs. The method of this activity is by providing counseling and screening questionnaires on the level of knowledge and attitudes of high school adolescents through the Ramadan pesantren at the Nurul Yaqin Lubuk Buaya Padang Mosque. The results of the program implementation are the implementation of counseling and education about smoking and drugs and their impact on society from the health and psychosocial aspects in the form of activity reports, documentation and publications.